2020
DOI: 10.1111/1462-2920.14972
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella persistence in soil depends on reciprocal interactions with indigenous microorganisms

Abstract: Summary Fresh fruits and vegetables have numerous benefits to human health. Unfortunately, their consumption is increasingly associated with food‐borne diseases, Salmonella enterica being their most frequent cause in Europe. Agricultural soils were postulated as reservoir of human pathogens, contributing to the contamination of crops during the growing period. Since the competition with the indigenous soil microbiota for colonization sites plays a major role in the success of invading species, we hypothesized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
37
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 44 publications
7
37
0
2
Order By: Relevance
“…The authors reported a significantly higher survival rate of Salmonella in soils with the organic amendment, reaching 91 dpi versus 35 dpi for control soils. Our study showed that the presence of Salmonella had no impact on the relative abundance of the soil microbiome on phylum level, which is in line with a previous study, which showed that Salmonella influenced the soil microbiome only when the prokaryotic diversity was very low [28].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The authors reported a significantly higher survival rate of Salmonella in soils with the organic amendment, reaching 91 dpi versus 35 dpi for control soils. Our study showed that the presence of Salmonella had no impact on the relative abundance of the soil microbiome on phylum level, which is in line with a previous study, which showed that Salmonella influenced the soil microbiome only when the prokaryotic diversity was very low [28].…”
Section: Discussionsupporting
confidence: 93%
“…In this scenario, we observe better Salmonella survival rates compared to control samples in which Salmonella was added to soil 28 days after fertilization. The results obtained in this study could be explained by the recent report by Schierstaedt et al [28], where it was demonstrated that the abundance of Salmonella enterica decreased faster in soils with a highly diverse prokaryotic community compared to soils with low diversity, underlying the importance of the native soil microbiome in suppressing pathogenic bacteria. Shah et al [58] investigated the persistence of S. Newport in soils with or without heat-treated chicken manure pellet amendment.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Habitat is being degraded and homogenized, and nutrient runoff from fertilizers and pesticide use are problematic in industrial-scale agricultural settings (Foley et al, 2005;Stocker et al, 2013). Under these circumstances, changes in soil microbial diversity and structure directly affect the persistence of human pathogens in the soil, such as Salmonella is more durable in high-temperature sterilized soil (Schierstaedt et al, 2020). Furthermore, the global mean surface temperature is increasing, which may contribute to prolonged droughts and flooding, and increased the probability of exposure to frozen pathogens.…”
Section: Changing Soil Healthmentioning
confidence: 99%
“…Meanwhile, global warming may facilitate the release of ancient pathogenic microorganisms and advance the population dynamics of viruses (Frenken et al, 2020;Labbé et al, 2020;Zhong et al, 2020), which can infect humans health through extreme weather or through the carriage of plants and animals. The soil pathogenic microbes, indigenous or exogenous pathogenic microbes in the soil that have the potential to cause disease to humans, are typically in balance with other microbes due to subtle interactions and soil properties, such as Salmonella, of which longevity in the soil depends on the interaction with indigenous microorganisms (Locatelli et al, 2013;Schierstaedt et al, 2020). However, this balance can be disrupted by the use of pesticides and fertilizers and by other types of industrial pollution, which may indirectly increase the competitive niche of pathogenic microbes and cause blooms, which increase the likelihood of outbreaks of disease in humans (Fig.…”
mentioning
confidence: 99%